Antifertility Effects of Ethanol-Extracted Turmeric on Male Rats: ELISA-Based Evaluation - Angrainy, Rizka; Elengoe, Asita; Ayakannu, Rathimalar; Irianti, Berliana; Israyati, Nur; Candra, Leon; Widodo, Muhammad Dedi (Indonesian Socety of Obstetrics and Gynecology, 2025)
AbstractObjective: To determine the effect of administering 96% ethanol extract of turmeric (Curcuma longa Linn, syn. Curcuma domestica Val.) on the antifertility effect on male rats. Methods: 18 Male and 18 Female Sprague-Dawley Rats were grouped into 6 Groups, namely the Control Group, Positive Control Group (Birth Control Pills), Treatment Group 1 with a dose of 25 mg/KgBW, Treatment Group 2 with a dose of 50 mg/KgBW, Treatment Group 3 with a dose of 25 mg/KgBW, Treatment Group Mating of Male and Female Rats given turmeric with a dose of 50 mg/KgBW, Treatment Group Mating of Male and Female Rats given turmeric is Male with a dose of 50 mg/KgBW. Turmeric extract was given orally every day for 30 days. Results: The data obtained were statistically analyzed using a one-way ANOVA test. Testosterone levels increased compared to the control group, indicating no significant difference, with a P value of 0.317 (p>0.05), and in vivo male sperm motility at doses of 25 mg/kgBW, 50 mg/kgBW, and 100 mg/kgBW was significantly different from the control group (p 0.00 < 0.05).Conclusion: Giving 96% turmeric ethanol extract (Curcuma longa Linn, syn. Curcuma domestica Val.) did not affect testosterone levels in male rats in vivo at doses of 25 mg/kgBW, 50 mg/kgBW, and 100 mg/kgBW, with a significance value of p 0.317 > 0.05, indicating no significant difference. Meanwhile, sperm motility testing showed a significant difference with a result of p = 0.00 < 0.05. For further research, it is hoped that further observations will be made regarding the potential of turmeric ethanol extract by conducting histological tests, and a mating test will be carried out as evidence of whether or not the treated rats are fertile. Keywords: antifertility, concentration testosterone, effectiveness, Sprague-Dawley Rats, turmeric extract.